Prevention village fund fraud in Indonesia: Moral sensitivity as a moderating variable - Sugeng Wahyudi; Tarmizi Achmad; Imang Dapit Pamungkas (Economies, 2022)
This study aims to examine the effectiveness of the internal control system, appropriate compensation, and the competency of the village apparatus regarding the prevention of village fund fraud with moral sensitivity as a moderating variable. This research is a quantitative method using hypothesis' inference to answer exploratory, descriptive, explanatory, and predictive analysis questions. Primary data are mainly used in this study. Data were collected using a survey method in a questionnaire with questions given to respondents to collect information. The sample of this research is the village office in 16 (sixteen) districts in Sumowono, Semarang Regency, Central Java, Indonesia, with 289 participants. Data analysis was carried out using Warp-PLS 7.0 application software. The results showed that the village apparatus's internal control system, appropriate compensation, and competency prevented village fund fraud. Furthermore, the novelty of this research is to add a moderating variable, moral sensitivity, which can strengthen the relationship between the internal control system, appropriate compensation, and competency of the village apparatus regarding the prevention of village fund fraud.
Keywords: 330; appropriate compensation; competency of village apparatus; internal control system; moral sensitivity; village fund fraud